Marijuana Policies in Drug Treatment Courts - Lu, Ruibin (Journal of drug issues, 2024)
Drug treatment courts are challenged by the ongoing trend of marijuana legalization. In states where it is legal for adult citizens to consume marijuana for medical and recreational purposes, treatment courts need to determine whether participants should be allowed to consume or possess marijuana. By analyzing the written policies of treatment courts in states that have legalized recreational and medical marijuana, this study explores how treatment courts address such challenges. The review shows a large percentage of drug treatment courts have yet to clearly communicate their marijuana policies with the participants in writing. However, among the drug treatment courts that have established marijuana-specific policies, the vast majority of courts continue to ban the use of marijuana while a few courts allow medical marijuana use on an individual basis.